2010
DOI: 10.1007/s00268-009-0387-6
|View full text |Cite
|
Sign up to set email alerts
|

[177Lu‐DOTA0‐Tyr3]‐Octreotate Treatment in Patients with Disseminated Gastroenteropancreatic Neuroendocrine Tumors: The Value of Measuring Absorbed Dose to the Kidney

Abstract: By using the absorbed dose to the kidneys as a limiting factor, treatment with (177)Lu-octreotate can be individualized, e.g., overtreatment can be avoided and patients with the potential to receive additional treatment can be identified. Further studies are needed to define tolerance doses to the kidneys so that treatment can be optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…First, organs and tumor overlap in many patients, and organs often contain tumor tissue, preventing exact uptake measurements (19)(20)(21). Furthermore, the organ sizes may vary substantially (20), and from 2D images it is not possible to estimate organ thicknesses or volumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, organs and tumor overlap in many patients, and organs often contain tumor tissue, preventing exact uptake measurements (19)(20)(21). Furthermore, the organ sizes may vary substantially (20), and from 2D images it is not possible to estimate organ thicknesses or volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported dosimetry data for the kidney based on 2-dimensional (2D) (1,8,16,18) or 3-dimensional (3D) (19)(20)(21)(22) imaging and attempted to tackle the question of the dose-limiting organ. In conventional external-beam radiotherapy, an absorbed dose limit of 23 Gy is used for the kidney (23).…”
mentioning
confidence: 99%
“…Systemic radionuclide therapy with the lutetium-177 labeled somatostatin analogue [DOTA 0 ,Tyr 3 ]octreotate ( 177 Lu-octreotate) has shown promising therapeutic results for patients with neuroendocrine (NE) tumors for whom effective treatment is limited [1][2][3][4][5]. A pronounced tumor reduction is observed in many patients, but complete tumor remission is rare [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…The limits for absorbed dose to the kidneys have been set at either 23 Gy (19,58) or 27 Gy (17,59). The use of the biologically effective dose allows for comparisons of therapies using a different number of cycles and other radionuclides such as 90 Y.…”
Section: Clinical Applications Of 177 Lumentioning
confidence: 99%